Organizational and personal factors as predictors of lecturers' organizational commitment in higher education institutions in Nigeria - Aji, Abubakar Abba; Abdul Hamid, Jamaliah; Hassan, Aminuddin; Mohd Rasdi, Roziah (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Organizational commitment concept in organizational development studies has generated a lot of interest among researchers in recent years, yet a deficiency is observed on predictors of employees’ commitment among lecturers in HEIs in Nigeria. Therefore, this study examines organizational and personal factors of organizational climate, organizational culture and psychological empowerment on organizational commitment among lecturers in Borno state. A quantitative method was used and base on the finding it was concluded that organizational culture was a better predictor of lecturers’ organizational commitment in HEIs, this paper offers recommendations for practice and research.